BS O03 Nutritional Complications After LaparoscopicRoux-en-Y Gastric Bypass and One-AnastomosisGastric Bypass: A Comparative Systematic Review and Meta-Analysis. (7th December 2022) - Salman, Mohamed; Noureldin, Khaled; Issa, Mohamed; Khalid, Sadaf; Tourkey, Mohamed; Elsherbiney, Mohammed; Gebril, Mahmoud; Salman, Ahmed; Shaaban, Hossam; Barkat, Tanzeela; Elhaj, Mujahid; Elewa, Ahmed
Abstract: Background: This systematic review and meta-analysis were done to assess the incidence of nutritional complications at follow-up after one-anastomosis gastric bypass (OAGB) and Roux-en-Y gastric bypass (RYGB). Methods: A systematic review and meta-analysis were carried out involving studies that compared the nutritional complications of Roux-en-Y gastric bypass (RYGB) and one-anastomosis gastric bypass (OAGB); these included the incidence of malnutrition as well as deficiencies of other nutritional elements, such as total protein, albumin, calcium, and iron. A comprehensive search strategy was implemented in PubMed, Embase, and the Cochrane Library. Effect sizes included the pooled odds ratios (ORs) and 95% confidence intervals (95% CIs), as well as mean differences (MDs) and 95% CIs of the percentage total weight loss (%TWL) and excess weight loss percentage (%EWL). Results: Thirteen studies were included (12, 964 patients, 66.27% females, 53.82% underwent OAGB). At the longest follow-up period (≥3 years), OAGB was associated with significantly higher %TWL (MD=5.41%, 95%CI, 1.52 to 9.29) and %EWL (MD=13.81%, 95%CI, 9.60 to 18.02) compared to RYGB. However, OAGB procedures were associated with malnutrition (OR=3.00, 95%CI, 1.68 to 5.36, p<0.0001), hypoalbuminemia (OR=2.38, 95%CI, 1.65 to 3.43, p<0.0001), hypoproteinemia (OR=1.85, 95%CI, 1.09 to 3.14, p=0.022), anemia (OR=1.38, 95%CI, 1.08 to 1.77, p=0.011), and hypocalcemia (OR=1.78, 95%CI, 1.01 to 3.12, p=0.046). On subgroup analyses, the proportions of anemia and hypoalbuminemia remained significantly higher at longer follow-up periods and in studies published in Asia. Conclusions: Despite the favorable weight loss profile, the unfavorable nutritional consequences of OAGB merit further investigations to explore the malabsorptive element, ethnic variation, and the role of the biliopancreatic limb length.